2006
DOI: 10.12968/npre.2006.4.11.22528
|View full text |Cite
|
Sign up to set email alerts
|

Reducing medication administration errors in learning disability nursing

Abstract: It is essential that people with a learning disability and mental disorder receive the appropriate medicines in order to promote both their physical and mental health. However, medication administration errors (MAEs) are relatively frequent occurrences, and can have serious consequences. There is mixed evidence as to whether they can be reduced through a two-nurse administration system. Two-nurse administration is relatively expensive, but could be more cost-effective if the second administrator were a special… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…[50] Logistic regression analysis determined that this type of error occurred on wards with fewer registered nurses or where there were patients with the same (or similar) names staying on the same unit. Finally, Dickens et al [52] (Supplemental Digital Content) found that using specially trained healthcare assistants as observers and checkers during the medication administration process reduced medication administration errors. Specifically, their retrospective study found a reduction in administration errors from 2.92% (of all prescribed doses) prior to implementing this observer system to 0.85% after this system had been implemented for 9 months.…”
Section: Administration (Nursing)mentioning
confidence: 99%
“…[50] Logistic regression analysis determined that this type of error occurred on wards with fewer registered nurses or where there were patients with the same (or similar) names staying on the same unit. Finally, Dickens et al [52] (Supplemental Digital Content) found that using specially trained healthcare assistants as observers and checkers during the medication administration process reduced medication administration errors. Specifically, their retrospective study found a reduction in administration errors from 2.92% (of all prescribed doses) prior to implementing this observer system to 0.85% after this system had been implemented for 9 months.…”
Section: Administration (Nursing)mentioning
confidence: 99%
“…If the second administrator was a specially trained health care assistant (HCA), it might be more cost‐effective. A recent study demonstrated a significant fall in the MAE rate when a trained HCA was introduced as an observer (Dickens et al. 2006/7).…”
Section: Analysing the Problemmentioning
confidence: 99%
“…However, finances are always tight in the National Health Service and so there is a call to be innovative. Medicine administration has always been the prerogative of the registered nurse, but this needs to be looked at creatively, as the Northampton team have performed (Dickens et al. 2006/7, 2008), to identify whether use of staff other than qualified nurses can improve patient care.…”
Section: System Changesmentioning
confidence: 99%
“…It is unsurprising, therefore, that studies examining UK‐registered nurses administering medication have identified a failure to apply biological and pharmacological theory to learning disability (Dickens et al . ), medical–surgical (Ndosi & Newell ), and mental health settings (Turner et al . ); however, due to the small sample size of these studies, their findings need to be treated with caution.…”
Section: Introductionmentioning
confidence: 99%
“…Another explanation is overreliance on the continuous assessment of medicinemanagement competencies of student nurses by busy, under-pressure clinical mentors across all nursing specialties (Bradshaw & Merriman 2008;Hunt 2011). It is unsurprising, therefore, that studies examining UKregistered nurses administering medication have identified a failure to apply biological and pharmacological theory to learning disability (Dickens et al 2006), medical-surgical (Ndosi & Newell 2009), and mental health settings (Turner et al 2007); however, due to the small sample size of these studies, their findings need to be treated with caution. It is also important to note that there are other explanations for nurses' shortcomings in administering medication, such as environmental distractions and inadequate medication documentation (Armitage & Knapman 2003;Hemingway et al 2011).…”
Section: Introductionmentioning
confidence: 99%